2013
DOI: 10.1186/1742-4755-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Why some women fail to give birth at health facilities: a qualitative study of women’s perceptions of perinatal care from rural Southern Malawi

Abstract: BackgroundDespite Malawi government’s policy to support women to deliver in health facilities with the assistance of skilled attendants, some women do not access this care.ObjectiveThe study explores the reasons why women delivered at home without skilled attendance despite receiving antenatal care at a health centre and their perceptions of perinatal care.MethodsA descriptive study design with qualitative data collection and analysis methods. Data were collected through face-to-face in-depth interviews using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
130
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 49 publications
23
130
2
3
Order By: Relevance
“…28 Some qualitative studies done in Malawi reveal negative attitudes among some nurses. 8,20,21 The differences in findings between these studies and the present study may be attributable to differences in the methodological approaches used in data collection. The positive attitudes of the nurses towards nursing care may have several possible explanations.…”
Section: Nurses' Attitudescontrasting
confidence: 67%
See 1 more Smart Citation
“…28 Some qualitative studies done in Malawi reveal negative attitudes among some nurses. 8,20,21 The differences in findings between these studies and the present study may be attributable to differences in the methodological approaches used in data collection. The positive attitudes of the nurses towards nursing care may have several possible explanations.…”
Section: Nurses' Attitudescontrasting
confidence: 67%
“…19 Studies conducted in Malawi have reported that negative attitudes among nurses are sometimes manifested by rudeness and scolding of patients. 8,20,21 Such behaviours are associated with job dissatisfaction among nurses. [22][23][24] Patient and public complaints about the quality of nursing care in Malawi may be related to negative attitudes among nurses who are dissatisfied with their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from previous studies investigating mothers who deliver at home in East Africa may be summarised by rural residency (Stephenson et al, 2006;Ng'anjo Phiri, et al, 2014;Yebyo et al, 2015), pastoralist communities (Yebyo et al, 2015), communities in poverty (Yebyo et al, 2015), real or perceived travel distances to a health facility (Shiferaw et al, 2013;Sipsma et al, 2013;Yebo et al, 2015) and unreliable transportation ser- o n l y mothers who delivered at home (38.4%, range, Mozambique 2.7% to Ethiopia 89.6%); home birthing was a significant risk factor for o n l y to Ethiopia 89.6%); home birthing was a significant risk factor for vices to a health facility (Shiferaw et al, 2013;Sipsma et al, 2013) especially during the rainy season (Kumbani et al, 2013). In addition, mothers who deliver at home may be characterised as those with fewer than 4 antenatal visits (Stephenson et al, 2006), those who are unable to pay for the high cost of maternity care (Stephenson et al, 2006;Shiferaw et al, 2013;Sipsma et al, 2013;Ng'anjo Phiri et al, 2014) and those who have concerns about the quality of maternity care (Sipsma et al, 2013), including health care worker's attitudes (Kumbani et al, 2013). Other factors may include religion -Protestant and Muslim in Tanzania, Protestant in Malawi (Johnson et al, 2013;Kumbani et al, 2013), husband's approval of family planning (Stephenson et al, 2006), the belief that it is not necessary or customary to attend a health care facility (Shiferaw et al, 2013) and pressure from husband or family members to deliver at home (Sipsma et al, 2013;Shiferaw 2013).…”
Section: East Africamentioning
confidence: 99%
“…In addition, mothers who deliver at home may be characterised as those with fewer than 4 antenatal visits (Stephenson et al, 2006), those who are unable to pay for the high cost of maternity care (Stephenson et al, 2006;Shiferaw et al, 2013;Sipsma et al, 2013;Ng'anjo Phiri et al, 2014) and those who have concerns about the quality of maternity care (Sipsma et al, 2013), including health care worker's attitudes (Kumbani et al, 2013). Other factors may include religion -Protestant and Muslim in Tanzania, Protestant in Malawi (Johnson et al, 2013;Kumbani et al, 2013), husband's approval of family planning (Stephenson et al, 2006), the belief that it is not necessary or customary to attend a health care facility (Shiferaw et al, 2013) and pressure from husband or family members to deliver at home (Sipsma et al, 2013;Shiferaw 2013). Finally, mothers reported birthing at home due to rapid labor (Kumbani et al, 2013), onset of labor at night (Kumbani et al, 2013), low education and low exposure to media (Yebyo et al, 2015) and not wanting to go to a health care facility alone (Stephenson et al, 2006).…”
Section: East Africamentioning
confidence: 99%
See 1 more Smart Citation